The unwritten rules and HIV: a qualitative study of informal institutions and HIV vulnerability among workers at social venues in Uganda - Susan Babirye; Susan Babirye; Susan Babirye; Kristien Michielsen; Freddie Ssengooba; Freddie Ssengooba (Frontiers in Public Health, 2023)
IntroductionThere is increasing appreciation of the need to understand how social and structural factors shape HIV risk. The unwritten rules, also known as informal institutions or social norms, are increasingly recognized as important determinants of HIV transmission. Unfortunately, these informal institutions, especially among high-risk environments for HIV, such as social venues like bars, lodges, remain poorly understood. This study explored the informal institutions at social venues, and how these institutions influenced vulnerability for HIV for venue workers in Uganda.MethodsWe conducted a qualitative study in two districts of Kyotera and Rakai in Central Uganda. We purposively selected and interviewed 44 workers including, cleaners, waiters, and waitresses and 22 venue managers at 22 social venues to explore the informal institutions at these establishments and how the institutions shaped HIV vulnerabilities among the workers. 31.8% (14) of the participants were males, and 68.2% (30) females. Data were analyzed using thematic content analysis.ResultsWe found that the informal institutions at the venues were both officially and socially created, communicated, and sanctioned. The most common institutions operated through; selective hiring, rigid reporting structures, and informal job contracting procedures. Meager salaries, varying and delayed payments as well as attractive benefits and bonuses from customers were also important forms of informal institutions at the venues. Drinking alcohol, and offering sexual services at the venues were acceptable, although excessive drinking, and committed sexual relationships with customers were disapproved. These informal institutions shaped a risk environment at the venues by creating risk exposure opportunities that influenced workers' engagement into sexual risk behaviors.ConclusionThe risk environment at social venues is shaped by the informal institutions at these venues. Thus, the need for venue-based HIV programs that integrate social norms interventions to better address the contextual determinants of HIV risk behaviors at the venues.